SHE’RIYATDA DIALOG VA UNING BADIIY FUNKSIYASI - Matyakupov, S. (SCIENCE and SOCIETY, 2024)
The article examines dialogue in poetry and its artistic function, the problem of the influence of artistic speech on the poetic structure of a poem. The study and originality of poetic speech in world literary criticism, issues of artistic communication in lyrics are also theoretically analyzed.